FEATURES OF THE COURSE OF PUBERTY IN GIRLS WITH LOW BIRTH WEIGHT - Mustafayeva, I.R. (World of Medicine and Biology, 2022)
65 girls in the pubertal period, living in the conditions of the city of Baku and Nakhchivan, were examined. The average age of the girls was 16.35±0.06 years. All girls were born at term with low body weight. The average weight of a newborn was 2.245±25.98 (1900–2500 g). In girls born with low body weight, a delay in physical and sexual development. The study of hormones revealed statistically significantly low levels of follicle-stimulating hormone (3.0±0.21 mIU/ml), luteinizing hormone (2.3±0.12 mIU/ml), ftee triyodtironin (2.56±0.08 pg/ml), free thyroxine (1.3±0.02 ng/ml), estradiol (30.0±0.9 pg/ml) and high levels of prolactin (17.9±0.22 ng/ml), thyroid–stimulating hormone (2.96±0.19 mIU/ml), dehydroepiandesterone sulfate (4.28±0.19 pg/ml), total testosterone (1.21±0.11 ng/ml), which reflected the presence of clinical and diagnostic manifestations of hypogonadotropic hypogonadism in this contingent of girls which affects the reproductive health of girls in subsequent periods of life.